Coverage of Agricultural Issues in Leading Indian Hindi Dailies: A Content Analysis (Indian Journal of Extension Education, 2025)
The majority of India’s population is directly or indirectly engaged in the agricultural sector. Currently, Indian agriculture is facing various challenges, but timely information dissemination is one of them. The present study was conducted to examine the agricultural issues published in two leading Hindi newspapers, i.e. Dainik Bhaskar and Amar Ujala. Editorials, opinion columns, and feature articles published in the Panipat edition of Haryana State during January 2023 and December 2023 were selected for the study. The study concluded that India’s highest-circulated Hindi newspapers, Dainik Bhaskar and Amar Ujala, published a limited number of agricultural issues. Both dailies have given the highest importance to national-level agricultural issues.